Implementasi Sistem Pencatatan Saldo Sedekah Jumat di Masjid Ar-Rahmat Berbasis Web - Mesra Betty Yel; Dadang Iskandar Mulyana; Jodi Juliansah; Muhammad Syahrul Fattah Ramadhan; Sahrul Hidayat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Ar-Rahmat Mosque has played an important role in the management of Muslim places of worship. However, to improve financial management, a more modern financial recording system is urgently needed. As a concrete step, the author carried out community service activities with a focus on implementing a system for recording Friday alms balances at the web-based Ar-Rahmat Mosque. The aim is to make it easier for the mosque's prosperity council to submit information on Friday alms balance reports and to facilitate the mosque's financial communication with the community. The author uses data collection techniques such as observation, interviews, and library research to design a system that is easy to use and can display accurate data. The designed information system includes financial data of the Ar-Rahmat Mosque. The author also tests the quality of the system by distributing questionnaires with a Likert scale of 1-5 to respondents. The calculation results show that the average score is 4.5 which indicates that the respondents agree with the application designed.